Modelagem digital de terreno do município de Graccho Cardoso, nordeste de Sergipe - Sardeiro, Simone Soraia Silva (2016)
In the Geographic Information Systems platform, Digital Terrain Model (DTM) is a mathematical way, to show a natural feature that occurs in the Earth's surface. The purpose of this dissertation was to build a digital terrain model for the municipality of Graccho Cardoso, approximate scale 1:65.000, and analyze their products (contour map, slope map, shading map, and geological and geomorphological maps superimposed on the digital terrain model). The city of Graccho Cardoso is located in the north of the state of Sergipe, at about 120 km away from Aracaju. The study area was selected to present geomorphological and geological diversity and have Satellite Images (SRTM) with good resolution for the selected working range. Graccho Cardoso occurs in quotas ranging between 140 m and 280 m above sea level, where the predominant pattern dendritic drainage. Since its relief is under the process planing and pediplanation. Its steepness varies from 0% to over 75%. Where there is a predominance with the angle of inclination between 3 and 45%. It has been more remarkable shading which fit fluvial channels, showing that the notching index or grain dissection is more pronounced. It has two types of morphostructures: Remnants Fold Roots (Sergipano Orogenic System – Proterozoic) and Sedimentary Basins and Covers (Superficial Formations – Fanerozoic). The results obtained by integration of the various maps shows up very similar to many traditional data mapping surveys.